Pengaruh Metode Pembelajaran Maharah Kalam Terhadap Pelajaran Bahasa Arab Pada Program Bimbingan Belajar: (Studi Kasus di MTs. Tarbiyatut Tholabah Lamongan) - Dini Maulidhah; Alya Khoironi Muhibbah; Faziadatun Ni’mah; Feni Tamimul Ummah; Mayaly Maghfiroh; Shofwatul Fikriyyah; Vika Madinatul Ilmi; Eny Lathifah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this study was to determine the effect of maharah kalam learning methods on Arabic language lessons in the tutoring programme at Madrsah Tsanawiyah Tarbiyatut Tholabah Lamongan. This research uses quantitative methods with the type of case study by maximising questionnaire instruments, interviews, observation, and documentation. The sample of this research is 30 students of class VIII MTs. Tarbiyatut Tholabah using data collection techniques by circulating questionnaires offline or directly and other instruments such as interviews, observation, documentation. The results of the analysis show that learning maharah kalam has a significant influence on the ability to speak Arabic in class VIII students at MTs. Tarbiyatut Tholabah Lamongan. With the calculation of the average participant response to the effectiveness of teaching and learning activities maharah kalam in class VIII students, with a percentage given by tutoring participants (bimbel) of 87.33%.